Novel Humanitarian Aid Program: The Glivec International Patient Assistance Program—Lessons Learned From Providing Access to Breakthrough Targeted Oncology Treatment in Low- and Middle-Income Countries - Garcia-Gonzalez, Pat (J Glob Oncol, 2015)
Imatinib was the first targeted therapy approved for the treatment of cancer. With its approval, it was immediately clear to Novartis that this breakthrough therapy would require an innovative approach to worldwide access, with special consideration of low- and middle-income countries. Lack of government reimbursement, universal health care, or health insurance coverage, few trained specialty physicians or diagnostic services, and poor health care infrastructure were, and continue to be, contributing barriers to access to treatment in low- and middle-income countries. The Glivec International Patient Assistance Program (GIPAP) is an international drug donation program established by Novartis Pharma AG and implemented in partnership with The Max Foundation, a nonprofit, nongovernmental organization. GIPAP was established in 2001, essentially in parallel with the first approval of imatinib for chronic myeloid leukemia. Since 2001, GIPAP has made imatinib accessible to all medically and financially eligible patients within 80 countries on an ongoing basis as long as their physicians prescribe it and no other means of access exists. To date, more than 49,000 patients have benefited from GIPAP, and 2.3 million monthly doses of imatinib have been approved through the program. GIPAP represents an innovative drug donation model that has set the standard for access programs for other targeted or innovative therapies. The purpose of this article is to describe the structure of GIPAP, as well as important lessons that have contributed to the success of the program. This article may assist other companies with the development of successful and far-reaching patient assistance programs in the future.